Associate Prof. Dr. Vengadesh A/l Periasamy, Associate Professor, Department of Physics, Faculty of Science, University of Malaya, 50603 Kuala Lumpur, MALAYSIA - Periasamy, Vengadesh (University of Malaya, 2018)
Researcher Profile Poster by Frontier Science Research Cluster (FSRC), University of Malaya.